2014
DOI: 10.1128/jvi.02862-13
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Hexokinase Is Increased by Its Interaction with Hepatitis C Virus Protein NS5A

Abstract: The study of cellular central carbon metabolism modulations induced by viruses is an emerging field. Human cytomegalovirus (HCMV), herpes simplex virus (HSV), Kaposi's sarcoma-associated herpesvirus (KSHV), and hepatitis C virus (HCV) have been shown recently to reprogram cell metabolism to support their replication. During HCV infection the global glucidolipidic metabolism of hepatocytes is highly impacted. It was suggested that HCV might modify glucose uptake and glycolysis to increase fatty acids synthesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 42 publications
2
96
1
1
Order By: Relevance
“…Viral replication may lead to the depletion of critical metabolite pools that could trigger a metabolic switch to increased aerobic glycolysis. However, a number of viral genes have been shown to specifically activate the glycolytic pathway in the absence of replication (11,44,47). Additionally, we recently found that VACV does not appear to induce glycolysis in the same cell type used in the present study (10), indicating that not all viruses activate glucose catabolism.…”
Section: Figmentioning
confidence: 71%
See 1 more Smart Citation
“…Viral replication may lead to the depletion of critical metabolite pools that could trigger a metabolic switch to increased aerobic glycolysis. However, a number of viral genes have been shown to specifically activate the glycolytic pathway in the absence of replication (11,44,47). Additionally, we recently found that VACV does not appear to induce glycolysis in the same cell type used in the present study (10), indicating that not all viruses activate glucose catabolism.…”
Section: Figmentioning
confidence: 71%
“…We show that GLUT1 and HK2 expression is upregulated in DENV-infected cells, with a concurrent increase in glucose uptake. Several viruses have been found to upregulate the expression and/or activity of GLUT1 and HK2 (11,32,(44)(45)(46), thus revealing common strategies viruses use to reprogram carbon metabolism. As many viruses induce glycolysis, it is possible that this metabolic alteration is simply a cellular response to infection.…”
Section: Figmentioning
confidence: 99%
“…The first study demonstrates that hepatitis C virus (HCV) non-estructural protein NS5A interacts with cellular hexokinase 2 inducing an enhancement of the catalytic parameters of the enzyme, which might explain the aerobic glycolysis shift observed in HCV-infected cells (Ramière et al, 2014). The second report shows that Mycobacterium tuberculosis Early-Secreted Antigenic Target (ESAT-6), a virulence factor and a secretory protein playing important roles in pathogenesis, interacts with the macrophage glycolytic enzymes alpha-enolase and phosphoglycerate kinase 1 (Singh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mayaro virus and herpes simplex virus 1 (HSV-1), for example, enhance glucose uptake and glycolytic flux by modulating the rate-limiting glycolytic enzyme 6-phosphofructo-1-kinase (PFK-1) (40,41). Hepatitis C virus (HCV), in turn, enhances glucose consumption and glycolytic flux through the interaction of viral NS5A with hexokinase 2 (HK2), the first rate-limiting enzyme of glycolysis (42). In this regard, we observed here that purified rNS1 increased ␤-NAD ϩ production and, consequently, GAPDH activity in vitro.…”
Section: Discussionmentioning
confidence: 99%